Developing Teaching Materials Using a Collaborative Learning Model to Improve Students' Understanding of Mathematical Concepts in Triangles and Quadranges - Lewa, Yusta Selvianjeli; Maria Carmelita Tali Wangge; Wilibaldus Bhoke; Melkior Wewe (Desimal: Jurnal Matematika, 2026)
This study addresses the persistent challenge of students’ low conceptual understanding in geometry, particularly in triangles and quadrilaterals, which is often attributed to the dominance of procedural teaching and limited collaborative engagement. Although collaborative learning and Realistic Mathematics Education have been widely examined, their integration into structured teaching materials remains underexplored, especially in facilitating deeper conceptual understanding. This study aims to develop and evaluate collaborative learning-based teaching materials grounded in a realistic mathematics approach to enhance students’ conceptual understanding. The research employed a Research and Development design using the ADDIE model, involving analysis, design, development, implementation, and evaluation stages. The participants were seventh-grade students at SMP Negeri 4 Bajawa. Data were collected through expert validation, classroom observation, and student and teacher response questionnaires, and analyzed using descriptive and inferential approaches. The findings indicate that the developed materials achieved high validity (96% from material experts and 100% from media experts) and strong practicality (student response 100% and teacher response 92%). Furthermore, the implementation results demonstrate a substantial improvement in students’ conceptual understanding, with an average achievement categorized as highly effective. These results suggest that integrating collaborative learning with realistic mathematical contexts provides a meaningful learning experience that supports active engagement and conceptual construction. This study contributes to mathematics education by offering an empirically validated instructional design that bridges collaborative interaction and contextual learning to improve conceptual understanding.